The Relationship between Body Image and Peer Social Support with Self-Confidence among Female Adolescents at Kendari State High School 2 - La Ode Liaumin Azim (Symbiohealth, 2026)
Self-confidence is one of the important factors in adolescent psychological development, especially in adolescent girls. Positive body image and peer social support play a significant role in shaping adolescent girls' self-confidence. This study aims to analyze the relationship between body image and peer social support with adolescent girls' self-confidence at Kendari 2 Public High School in 2025. The study employed a quantitative design using the person corelation method and a cross-sectional approach. The sample consisted of 58 adolescent girls selected using total sampling technique. Data analysis was performed using chi square test to determine the relationship between these variables. The results showed a relationship between body image and self-confidence (p-value = 0.000 < 0.05) and peer social support and self-confidence (p-value = 0.001 < 0.05), thus accepting Ha. Body image and peer social support have a significant influence on the self-confidence of adolescent girls. This study implies the importance of improving positive body image and strong social support in supporting the development of self-confidence in adolescent girls in the school environment.